A Rapid and Universal Workflow for Label‐Free‐Quantitation‐Based Proteomic and Phosphoproteomic Studies in Cereals. Issue 6 (8th June 2022) - He, Mingjie; Wang, Jiahui; Herold, Sandra; Xi, Lin; Schulze, Waltraud X.
Abstract: Proteomics and phosphoproteomics are robust tools to analyze dynamics of post‐transcriptional processes during growth and development. A variety of experimental methods and workflows have been published, but most of them were developed for model plants and have not been adapted to high‐throughput platforms. Here, we describe an experimental workflow for proteome and phosphoproteome studies tailored to cereal crop tissues. The workflow consists of two parallel parts that are suitable for analyzing protein/phosphoprotein from total proteins and the microsomal membrane fraction. We present phosphoproteomic data regarding quantification coverage and analytical reproducibility for example preparations from maize root and shoot, wheat leaf, and a microsomal protein preparation from maize leaf. To enable users to adjust for tissue specific requirements, we provide two different methods of protein clean‐up: traditional ethanol precipitation (PC) and a recently developed technology termed single‐pot, solid‐phase‐enhanced sample preparation (SP3). Both the PC and SP3 methods are effective in the removal of unwanted substances in total protein crude extracts. In addition, two different methods of phosphopeptide enrichment are presented: a TiO2 ‐based method and Fe(III)‐NTA cartridges on a robotized platform. Although the overall number of phosphopeptides is stable across protein clean‐up and phosphopeptide enrichment methods, there are differences in the preferred phosphopeptides in each enrichment method. The preferred protocol depends on laboratory capabilities and research objective. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Total protein crude extraction Basic Protocol 2 : Total protein clean‐up with ethanol precipitation Alternate Protocol 1 : Total protein clean‐up with SP3 method Basic Protocol 3 : Microsomal fraction protein extraction Basic Protocol 4 : Protein concentration determination by Bradford assay Basic Protocol 5 : In‐solution digestion with trypsin Basic Protocol 6 : Phosphopeptide enrichment with TiO2 Alternate Protocol 2 : Phosphopeptide enrichment with Fe(III)‐NTA cartridges Basic Protocol 7 : Peptide desalting with C18 material Basic Protocol 8 : LC‐MS/MS analysis of (phospho)peptides and spectrum matching